The effect of using A Designed Equipment to Develop Motor Response of Young Soccer Players - Ali, Mohammed (Journal of Physical Education, 2014)
The introduction and the importance of the research, addressed the development that is happening in the world through the scientific revolution in sports science and the role of the devices in raising the level of the sports and the output achieved, as well as the diversity in the use of means of training in the different modern sports , especially in soccer . The problem of the research lies in the need of a design to development the response speed. The objectives of the research are: Designing a device to develop the motor and the speed of response speed and setting exercises by the device. There are statistical differences between the pre and post tests of the two sets of the study in favor of the pre tests and the experimental group. The Research domains domain represented by the(20) young players of Al-Nafot soccer team which . The researcher used the experimental method applied on (20) players divided into control and experimental groups. It included exercises, experimental experience, pre test, statistical means, and post test. The statistical processing results and its analysis sorted in tables were shown. It is concluded that the use of devices and visual stimuli has an important and positive role in the development of the motor speed of response. Which is recommended in this study